Effects of agency costs on the relationship between tax avoidance and firm value: A case of Chinese companies - Yoon, SungMan; Xin, JiaQi; Cui, Ying (Journal of Social Economics Research, 2024)
This study aims to examine the impact of agency costs on the relationship between tax avoidance and firm value in Chinese companies. Generally, a positive relationship exists between corporate tax avoidance and firm value when a company’s internal controls are robust and managerial incentives towards shareholder rights are significant. However, engaging in tax avoidance doesn’t guarantee an automatic improvement in firm value. Companies need to carefully evaluate the revenue generated and the costs incurred due to agency issues when making tax-avoidance decisions that benefit the company’s growth. The main findings of the study are as follows: First, there is a statistically significant positive relationship between tax avoidance and firm value. This implies that the tax savings resulting from tax avoidance lead to an increase in firm value, either through efficient investment or through higher shareholder returns. Second, as CEO (Chief Executive Officer) agency costs increase, the relationship between tax avoidance and firm value is attenuated. This suggests that the tax savings from tax avoidance are offset by CEO agency costs, or that the purpose of tax avoidance is related to opportunistic behaviour rather than increasing firm value. The findings of this study highlight the importance of enhancing corporate governance to decrease agency costs and the significance of reducing information asymmetry between internal and external entities within the company. This will help effectively utilize tax savings from tax avoidance for firm investment.